Pertanggungjawaban Pidana PH Yang Menghalangi Pencarian Berita Dengan Kekerasan Di Tinjau Dari Kitab Undang-Undang Hukum Pidana - Irvan Haris Fuariputra (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2021)
Abstract- purpose writing this as a requirement for graduation and get a law degree at the Faculty of Law, University of Surabaya. The practical purpose is to determine and analyze the defense was forced to Article 49 paragraph (1) of the Criminal Code against obstructing PH news searches by violence forced the defense to be the reason that has been applied to the PH can be a reason for the acquittal by the Supreme Court. The results showed relation to the application of Article 49 paragraph (1) attack is a sudden and immediate attack by a previously unknown victim and performed in real time at the time. At the time of the incident the journalists simply take a picture (photo) as well as looking for information or news about the PH delegation at that time undergoing phase II, the journalists do their job responsibly. It is the journalists to take pictures (photos) PH distances are used. The journalists from taking pictures (photos) and search for information or news about PH at the time involved in the case, based on Article 1 paragraph 1 of the Press Law, it is not an act or offense which is against the law. The reporters simply take a picture (photo) as well as looking for information or news about PH stand trial at that time. It's just that at that time he did not like to be covered by the media, PH defend themselves. But self-defense is performed by only a refusal to PH would not be covered by the media and does not refer to self-defense under Article 49 paragraph (1) of the Criminal Code. The way the defense is worth if there is no other way to do, but PH prefer to defend the conduct prohibited by the Act. Keywords: Criminal Liability, Obstructing Searched News, With Violence.